1998
DOI: 10.1109/58.646926
|View full text |Cite
|
Sign up to set email alerts
|

Thermal dose optimization via temporal switching in ultrasound surgery

Abstract: Temporal switching has been simulated and implemented in vivo experiments as a method to optimize thermal dose in ultrasound surgery. By optimizing the thermal dose over a tissue volume, the peak temperature is decreased, less average power is expended, and overall treatment time is shortened. To test this hypothesis, a 16 element, spherically sectioned array has been constructed for application in ultrasound surgery guided by magnetic resonance imaging. A simulation study for the array was performed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 22 publications
0
54
0
Order By: Relevance
“…The temperature and TD maps (evaluated with the use of Sapareto's equation (7,8)), were superimposed on magnitude images to visualize the spatial extension of the thermal treatment during the ablation.…”
Section: Temperature Mri Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature and TD maps (evaluated with the use of Sapareto's equation (7,8)), were superimposed on magnitude images to visualize the spatial extension of the thermal treatment during the ablation.…”
Section: Temperature Mri Protocolmentioning
confidence: 99%
“…However, the limited precision of such images necessitates the acquisition of dynamic gadolinium (Gd)-enhanced T1-weighted (T1w) images at the end of the procedure (6). MRI may also provide temperature imaging for quantitative monitoring based on the thermal dose (TD) concept (7,8). Thus, several MR thermometry methods have been developed (9).…”
mentioning
confidence: 99%
“…Indeed, previous studies have indicated that MRgHIFU treatment times can be reduced through the use of phased array transducers. [1][2][3] For effective, accurate and fast thermal treatments, the design objectives for a phased array transducer include a small focal spot size, suppressing grating lobes and side lobes, maximizing the range of electronic steering in 3D and achieving maximum pressure at the focal zone. 4 These objectives are achieved by manipulating the frequency of operation, radius of curvature, number of elements, interelement spacing, element size, and aperture diameter of the transducer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, optimal multiple-focus patterns which produce a clean ultrasound field can serve as the basis for temporal switching. The previous studies [1,5,6,11] mainly used the predefined multiple focus patterns where the spacing between adjacent focal points was close. Besides, a single pattern with four foci or double patterns with four and five foci were repeatedly scanned in a raster fashion like a single-focus scan.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal switching technique [1,4,5] is to rapidly switch between patterns for sequentially multiple focusing to increase the effective focal volume. By the way, the larger the number of focal points used, the more likely it is that the ultrasound field will have unexpected hot spots.…”
Section: Introductionmentioning
confidence: 99%